THE PREDICTOR FACTORS OF EMERGENCY NURSES' PERFORMANCES TO THE PROFESSIONAL SERVICES EXCELLENCE - Rina Annisa (CNJ: Caring Nursing Journal, 2017)
Emergency nurses’ performances remains long standing determinates of quality services rendered for patients admitted to get emergency treatments in the hospitals. It has been viewed as a dimension of professional services excellence. The purpose of this study focused on the predictive correlation of five predictors; namely human resources management, transformational leadership, incentives, hospital structure, and job rotation on the emergency nurses’ performance. This descriptive quantitative study used total sampling technique of 100 nurses in the Emergency Department, in four Government Hospital in Banjarmasin, Bajarbaru, and Martapura. All data obtained by administering questionnaires to the participances. The analytical procedure of multiple linear regression was utilized to determine the predicting strength correlation between the dependent and the independent variables. The result of Pearson product‑moment correlation coefficients revealed that positive correlation established between emergency nurses’ performances and human resources management, transformational leadership, incentives, hospital structure, and job rotation, as the independent variables. The summary of multiple linear regression analysis of all independent variables indicated that incentives was the most strongly predictor to the emergency nurses’ performances.